2008
DOI: 10.1097/01.jac.0000336556.54460.25
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Disaster Preparedness and Surge Capacity in Emergency Facility Planning

Abstract: The ability to adapt and utilize emergency facilities is a critical element in responding to surges resulting from man-made and natural events. The current stresses on emergency services throughout the country find few adequately prepared to effectively absorb a sudden increase in patients along with some of the potential special requirements, such as quarantining of epidemic patients and mass decontamination. This article reviews major findings of the federally funded ER One project, a research initiative tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Many publications have reported using DES for process redesign and optimization (Baril, Gascon, Miller, & Co ˆte ´, 2016;Rutberg, Wenczel, Devaney, Goldlust, & Day, 2015), staff scheduling (Rossetti, Trzcinski, & Syverud, 1999), resource allocation for staffing (Koyuncu, Araz, Zeger, & Damien, 2017) and equipment (Lo ´pez-Valca ´rcel & Pe ´rez, 1994); scheduling patients and procedures in outpatient (Cayirli, Veral, & Rosen, 2006) and surgical units (Saadouli, Jerbi, Dammak, Masmoudi, & Bouaziz, 2015); managing patient admission in inpatient units (Griffiths, Jones, Read, & Williams, 2010); and using ancillary resource such as labs, pharmacies, and imaging departments (Reynolds et al, 2011). Moreover, DES has been proven to be effective in planning and design of healthcare facilities, such as sizing and surge capacity planning for facility (Saunders, 2010;Zilm, Berry, Pietrzak, & Paratore, 2008), exam rooms (Wiinamaki & Dronzek, 2003), patient beds (Rodrigues, Zaric, & Stanford, 2017;Zhu, Hen, & Teow, 2012), and operating rooms (ORs; Wullink et al, 2007). For instance, O'Hara (2014) demonstrated that using DES to integrate the clinical operations in architectural design process is able to optimize the performance of an intensive care unit (ICU).…”
Section: Applications Of Des In Healthcarementioning
confidence: 99%
“…Many publications have reported using DES for process redesign and optimization (Baril, Gascon, Miller, & Co ˆte ´, 2016;Rutberg, Wenczel, Devaney, Goldlust, & Day, 2015), staff scheduling (Rossetti, Trzcinski, & Syverud, 1999), resource allocation for staffing (Koyuncu, Araz, Zeger, & Damien, 2017) and equipment (Lo ´pez-Valca ´rcel & Pe ´rez, 1994); scheduling patients and procedures in outpatient (Cayirli, Veral, & Rosen, 2006) and surgical units (Saadouli, Jerbi, Dammak, Masmoudi, & Bouaziz, 2015); managing patient admission in inpatient units (Griffiths, Jones, Read, & Williams, 2010); and using ancillary resource such as labs, pharmacies, and imaging departments (Reynolds et al, 2011). Moreover, DES has been proven to be effective in planning and design of healthcare facilities, such as sizing and surge capacity planning for facility (Saunders, 2010;Zilm, Berry, Pietrzak, & Paratore, 2008), exam rooms (Wiinamaki & Dronzek, 2003), patient beds (Rodrigues, Zaric, & Stanford, 2017;Zhu, Hen, & Teow, 2012), and operating rooms (ORs; Wullink et al, 2007). For instance, O'Hara (2014) demonstrated that using DES to integrate the clinical operations in architectural design process is able to optimize the performance of an intensive care unit (ICU).…”
Section: Applications Of Des In Healthcarementioning
confidence: 99%
“…If the design of treatment spaces in an ED is highly specialized to the extent that it limits the delivery of different types of care, the operational flexibility of the ED will be constrained (Huddy & McKay, 1996). The utilization of acuity adaptable rooms (Zilm et al, 2008), where various types of care can be provided, can address this issue. The literature has identified several design strategies that can potentially enable seamless switching between two or multiple modes of operation to accommodate care at different acuity levels.…”
Section: Modifiabilitymentioning
confidence: 99%
“…While various factors may contribute to this low percentage, one potential explanation is the lack of versatility in the nonclinical areas examined. Therefore, it seems crucial to enhance the versatility of nonclinical spaces during the design process to ensure their seamless adaptability for other purposes (e.g., treatment purposes) without the need for additional construction (Zilm et al, 2008). The identified design solutions regarding versatility are reported in the subsequent paragraph.…”
Section: Versatilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Scalability concerns the capability of emergency management systems to quickly scale-up to accommodate large-scale incidents and is typically achieved through systematic preparing and planning. Medical Emergency Response facilities are usually organized with this in mind and may serve as inspiration for other sectors in emergency management (Zilm et al 2008). The aim of scalability is to maintain a sufficient, but not excessive level of staff, equipment, etc., to deal with everyday incidents, while at the same time cultivating a system that can manage large-scale incidents.…”
Section: Scalabilitymentioning
confidence: 99%